Effect of Organic Manure and Crop Residue Based Long-Term Nutrient Management Systems on Soil Quality Changes under Sole Finger Millet (Eleusine coracana (L.) Gaertn.) and Groundnut (Arachis hypogaea L.) – Finger Millet Rotation in Rainfed Alfisol. Issue 7 (11th April 2016) - Sharma, K. L.; Ramachandrappa, B. K.; Chandrika, D. Suma; Sathish, A.; Dhanpal, G. N.; Rao, Ch. Srinivasa; Shankar, M. A.; Grace, J. Kusuma; Sankar, G. R. Maruthi; Chary, G. Ravindra; Munnalal,; Kumar, T. Satish; et al.
ABSTRACT: A long-term experiment was conducted to evaluate the effect of integrated use of organic and inorganic sources of nutrients on soil quality and its relation to finger millet yield under two predominant crop rotations viz., groundnut–finger millet and finger millet monocropping in hot moist semiarid rainfed Alfisol soils in South India. Two experiments were laid out separately for each cropping system in a randomized complete block design with five treatments individually with FYM and maize residue-based combinations viz., Control (T1), FYM @ 10t ha −1 or Maize residue (MR) @ 5t ha −1 (T2), farm yard manure (FYM) @ 10t ha −1 or Maize residue (MR) @ 5t ha −1  + 50% RDF (Recommended Fertiliser Dose) N, P2 O5 & K2 O (T3), FYM @ 10t ha −1 or Maize residue (MR) @ 5t ha −1  + 100% RDF N, P2 O5 & K2 O (T4), Recommended N, P2 O5 & K2 O (T5). Thus, four sets of nutrient management systems were evaluated. The results showed that farm yard manure or maize residue application in combination with recommended dose of fertilizer significantly improved the soil physical, chemical, and biological properties compared to control and application of inorganic fertilizers alone. Based on evaluation of 19 soil quality parameters under each of the four nutrient management systems, the common key soil quality indicators emerged out were: organic C (OC), available nitrogen (N), available sulfur (S), and mean weight diameter (MWD) of soil aggregates. A significant correlation between the finger millet yield and the relative soil quality indices (RSQI) indicates the importance of soil quality in these semiarid Alfisol soils. The results and the methodology adopted in the present study could be of importance in improving the soil quality not only for the region of the study, but also in other identical soils and cropping systems across the world.